Challenges in the diagnostics and management of hydrochlorothiazide-induced severe hyponatremia in a habitual beer drinker - Laubner, Gabija; Gintautaitė, Gabija; Badaras, Robertas (Acta medica Lituanica, 2020)
Introduction. Beer potomania is a syndrome of severe hyponatremia caused by excessive beer consumption. The risk of hyponatremia increases in the case of a combination of beer potomania and the use of thiazide diuretics. Case report. A 55-year-old male patient with the anamnesis of a long-lasting alcohol use disorder was presented to the emergency department after seizures accompanied by an impaired mental status. He had been drinking beer regularly for ten years. On physical examination, the patient was tachypneic, tachycardic, disorientated, restless, the Glasgow Coma Scale score of 9, observed tremor, and the smell of alcohol from the mouth. Laboratory results showed plasma sodium 105 mmol/L, blood urea nitrogen 1.8 mmol/L, the alcohol concentration in the blood 0.06 g/l, and calculated serum osmolality 219 mOsm/kg H2O. After a detailed initial evaluation of the patient and labs for hyponatremia, a diagnosis of beer potomania was established. On the third day of hospitalization, the patient’s anamnesis was filled with information about the use of Valsartan/hydrochlorothiazide, together with reduced salt intake in the diet for three months for arterial hypertension treatment. It was decided that the combination of heavy beer drinking with the use of diuretic and reduced consumption of salt provoked hyponatremia. The patient was treated with infusion therapy of sodium chloride; plasma sodium level reached 136 on the third day of treatment. Conclusions. This case represents an unusual syndrome of beer potomania in conjunction with hydrochlorothiazide usage and reduced salt consumption, which can result in severe hyponatremia that may provoke severe neurologic damage.